A Randomized, Double‐Blind, Placebo‐Controlled, Phase II Study of Regorafenib Versus Placebo in Advanced/Metastatic, Treatment‐Refractory Liposarcoma: Results from the SARC024 Study. (20th August 2020) - Riedel, Richard F.; Ballman, Karla V.; Lu, Yao; Attia, Steven; Loggers, Elizabeth T.; Ganjoo, Kristen N.; Livingston, Michael B.; Chow, Warren; Wright, Jennifer; Ward, John H.; Rushing, Daniel; Okuno, Scott H.; et al.
Abstract: Trial Information: ClinicalTrials.gov  Identifier : NCT02048371 Sponsors : SARC, with support from Bayer HealthCare Pharmaceuticals (Berlin, Germany) Principal Investigator : Richard F. Riedel IRB Approved : Yes Click here to access other published clinical trials . Lessons Learned : The results from the liposarcoma cohort of SARC024 confirm previously published data and do not support the routine use of regorafenib in this patient population. Continued exploration of novel therapies, including combination approaches, is warranted for a patient population in whom limited treatment options exist. Background: Regorafenib is a multitargeted kinase inhibitor with a kinase profile overlapping, but distinct from, pazopanib, an agent approved for recurrent and metastatic non‐gastrointestinal stromal tumor (GIST), non‐adipocytic soft tissue sarcoma. We conducted a randomized, phase II study of regorafenib versus placebo in refractory liposarcoma patients. Methods: Patients with advanced or metastatic, treatment‐refractory liposarcoma were randomized 1:1 to receive regorafenib 160 mg or placebo once daily (3 weeks on, 1 week off). Patients with well‐differentiated liposarcoma only were excluded. Crossover for placebo was allowed upon progression. The primary endpoint was progression‐free survival (PFS), according to RECIST version 1.1. Results: Forty‐eight subjects with liposarcoma (34 dedifferentiated, 12 myxoid/round cell, 2 pleomorphic) were enrolled. Median PFS was 1.87 (95% confidence interval [CI], 0.92–3.67) months for regorafenib versus 2.07 (95% CI, 1.64–3.44) months for placebo; stratified hazard ratio [HR], 0.85 (95% CI, 0.46, 1.58), p = .62. No responses were seen on regorafenib. One PR was observed on placebo. Median overall survival was 6.46 (95% CI, 4.16–23.48) months for regorafenib and 4.89 (95% CI, 3.02–9.77) months for placebo, stratified HR, 0.66 (95% CI, 0.31–1.40), p = .28). Treatment‐related adverse events were similar to the known safety profile of regorafenib. Conclusion: Regorafenib did not appear to improve PFS in treatment‐refractory liposarcoma. No new significant safety signals were observed.